The World War Two reader - Martel, Gordon 1946- Hrsg (Routledge, 2004)
The fall of France, 1940 / Martin S. Alexander -- Mobilization for total war in Germany 1939-1941 / Richard Overy -- Hiroshima : a strategy of shock / Lawrence Freedman and Saki Dockrill -- Ideology, calculation, and improvisation : spheres of influence and Soviet foreign policy 1939-1945 / Geoffrey Roberts -- The Third Reich reflected : German civil administration in the occupied Soviet Union, 1941-44 / Jonathan Steinberg -- This is the army : imagining a democratic military in World War II / Benjamin L. Alpers -- You cannot hate the bastard who is trying to kill you-- : combat and ideology in the British army in the war against Germany, 1939-45 / David French -- "Ordinary men" or "ideological soldiers"? Police battalion 310 in Russia, 1942 / Edward B. Westermann -- Race, language, and war in two cultures : World war II in Asia / John Dower -- Women in combat : the World War II experience in the United States, Great Britain, Germany, and the Soviet Union / D'ann Campbell -- Nazism, modern war and rural society in Württemberg, 1939-45 / Jill Stephenson -- Partisanes and gender politics in Vichy France / Paula Schwartz -- War and social history : Britain and the home front during the Second World War / Jose Harris -- The politics of sacrifice on the American home front in World War II / Mark H. Leff -- Female desires : the meaning of World War II / Marilyn Lake -- Victims of genocide and national memory : Belgium, France and the Netherlands 1945-1965 / Pieter Lagrou -- Making histories : experiencing the Blitz in London's museums in the 1990s / Lucy Noakes -- Saving Private Ryan and postwar memory in America / John Bodnar -- Transformative knowledge and postnationalist public spheres : the Smithsonian Enola Gay controversy / Lisa Yoneyama